De baixo para cima: implicações socioespaciais da transferência da feira livre na (re)produção do espaço urbano de Nova Cruz-RN (1991-2010) - Lima, Bruno Luiz Philip de (2010)
The present work is about the reproduction of the urban area of Nova Cruz RN, with the objective of analyzing the social and spatial implications of the relocation of the main street market in the city from 1991 on. Nowadays, the city of Nova Cruz takes over importance in the potiguar social and spatial scenario due to its condition of central city which is practiced for decades in Potiguar Agreste Microregion. Beginning with its formation process connected with traveler‟s hostel which assisted the activity of cattle transportation, further in time by the golden era of cotton production in its territory, it was noticed that its importance in relation with the nearby towns has been happening differently throughout time. From the year 1991 on, the town of Nova Cruz has gone through a territory restructuring of its urban area due to the relocation of the open market from Downtown neighborhood to São Sebastião neighborhood. Such territorial movement resulted in a reformation of the town‟s urban space, promoting in both neighborhoods urban growth and the expansion of commercial activity associated with the migration of the commercial center of the city. The transference of the commercial area has caused these processes through the new uses of the land towards the São Sebastião region, it has also caused a decrease in market value of the downtown area as a result of the breakdown of previous existing business activities, their service contribution and the citizen migration, establishing a space and socioeconomic portrait in the neighborhood. From this context, our analysis seeks to understand the social and spatial impacts occurred in Downtown neighborhood, the way in which the production and reproduction of the urban space in São Sebastião neighborhood and the implications resulted from the actions of the administrative power in restructuring of the urban space of Nova Cruz. In order to do so, a bibliographical research was used to compose our theoretic-conceptual mark, discussing the matter with authors such as Roberto Lobato Corrêa, Ana Fani, Milton Santos, Manuel Castells e Heri Lefvbre, among others, discussing on the subject of urban analysis, the concepts of urban space and the process of reproduction of the urban space. A field research was utilized in our area of study by means of primary data gathering through interviews, questionnaire and photographic register. Secondary data gathering was also obtained by means of bibliographical and documental research related to our study object. By these means, it was sought to contribute to the understanding of the urban space through its production and reproduction based upon the discovery of social and spatial practices